Delineating Potential Hydrocarbon Targets Through Aero-Radiometric Techniques - Bello Y Ayoola; Mohammed B Yakubu; Muhammad A Bilal (Physics Access)
The discovery of more hydrocarbon wells remains a major recipe to boost the economy of Nigeria, a major oil producer in Africa. The seismic method is prominent for identifying traps in the oil explorations, but cannot indicate if the trap host hydrocarbon. This gap is usually filled by the radiometric method, its characteristics around the Kolmani well 1 have hitherto not been reported. This research focused on identifying promising locations for hydrocarbon accumulation around the Kolmani Well 1 while using the well as a control. To achieve the objectives of this research, the nature of the radioelements was observed over the Kolmani well1 and the outcome of normalizing potential and uranium was also identified. The average values of potassium (K), thorium (Th), and uranium (U) are 0.277%, 8.917 ppm, and 1.431 ppm respectively. The concentration of the three radioelements, K, Th, and U, decreases over the oil well. This was ascribed to enhanced leaching of natural radioelements caused by hydrocarbon-generated groundwater acids. The result of the normalization of K with Th yields a low concentration of K over the Kolmani well1 and the normalization of U with Th yields a high concentration of U over the Kolmani well1. These were in tandem with the report on the application of the method in previous locations. Hence, the results of the normalization of K and U were used to identify four locations with potential for hydrocarbon exploration. The viability of these locations was confirmed with the positive DRAD (Delineation of Radiometric anomalies) value (ranging from -5.1 to +5.2), a pointer to hydrocarbon accumulation in an area, recorded in these locations and the location of the Kolmani well 1.